Currency Runs, International Reserves Management and Optimal Monetary Policy Rules - Mika Kato; Christian R. Proa\~no; Willi Semmler (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
This paper studies the design of optimal monetary policy rules for emerging economies confronted to sharp capital outflows and speculative attacks. We extend Taylor type monetary policy rules by allowing the central bank to give some weight to the level of precautionary foreign reserve balances as one of its targets. We show that a currency crisis scenario can easily occur when the weight is zero, and that it can be avoided when the weight is positive. The impacts of the central bank's monetary control on the output level, the inflation rate, the exchange rate, and the foreign reserve level are investigated as well. By applying both the Hamiltonian as well as the Hamilton-Jacobi-Bellman (HJB) equation (the latter leading to a dynamic programming formulation of the problem), we can explore safe domains of attractions in a variety of complicated model variants. Given the uncertainties the central banks faces, we also show of how central banks can enlarge safe domains of attraction.
urn:nbn:de:101:1-20091104844
Keywords: E5; F3; 330; Currency Crises; Capital Outflows; Monetary Policy Rules